Edukasi Sosial Sebagai Langkah Awal Menumbuhkan Kesadaran Anti-Bullying dan Mengenalkan Pendidikan Seksual Pada Anak di SDN Rejoso, Kabupaten Nganjuk - Chrystia Aji Putra; Rania Anjati Aurellia Putri; Eka Maidhatul Jannah; Rahmania Ainur Fitri; Ramadhan Dwi Setyawan (Pusat Riset dan Inovasi Nasional, 2024)
Bullying and social violence problems against children in Rejoso Village are ongoing issues that need to be addressed. The school consistently addresses the issues regarding bullying and sexual violence by implementing sanctions and providing special attention to these students. Even though, in their progress these efforts may fail. This community service a project aims to raise awareness about anti-bullying and sexual education through social education activities for children at SDN Rejoso, Nganjuk Regency. The psychoeducation method is applied in this social education activity. The goal is to educating students at SDN Rejoso, Nganjuk Regency, about these topics and make them understanding it. The results shows that the students at SDN Rejoso can understand the anti-bullying and sexual education materials, therefore in the field, there is some a problem like the tools for presentation is insufficient and several class are unable to accommodate a large number of participants.